Development of a Measuring Instrument for the Level of Integrity of Prospective Religious Teachers Based on Personality Competence - Amaliyah, Amaliyah; Nurpratiwi, suci; Effendi, Muhamad Ridwan; Narulita, Sari (Proceeding International Conference on Religion, Science and Education, 2024)
The aim of this research is to measure the level of personality competency integrity of prospective Islamic religious education teachers. Also, it aims to develop a valid competency assessment instrument for prospective teachers that will measure the integrity of the personality competencies of prospective Islamic religious education teachers. Pedagogical competence tends to be the dominant focus of competency assessment for prospective Islamic religious education teachers, however, it is important for future Islamic religious education teachers to also receive strengthening of personality competence. Empowering the personal competence of prospective Islamic religious educators can be achieved through the practice and implementation of micro teaching and internships, because integrity must be developed and nurtured through self-awareness. the integrity of a religious teacher on personality competence as an evaluative component in producing professional and competent teachers who become role models for students. The study participants comprised students from the Islamic Education Study Program at the State University of Jakarta who were conducting teaching internships in schools. The study employed a descriptive quantitative research method, used a questionnaire to collect data and validity and reliability tests to analysis data. The results of this research describe the various levels of integrity of prospective religious education teachers and the results of testing the validity and reliability of measuring instruments.